Vagally mediated atrioventricular block: pathophysiology and diagnosis. Issue 13 (2nd January 2013) - Alboni, Paolo; Holz, Anna; Brignole, Michele
Abstract : Vagally mediated atrioventricular (AV) block is defined as a paroxysmal AV block, localised within the AV node, associated with slowing of the sinus rate. All types of second-degree AV block, including pseudo-Mobitz II block, and complete AV block, may be present. Most of the patients have normal AV conduction. Differential diagnosis with intrinsic AV block is based on the behaviour of the sinus rate. Vagally mediated AV block is benign; it can be recorded as an asymptomatic or symptomatic event (syncope/presyncope). Syncope due to this form of AV block should be diagnosed and managed as neurally mediated syncope. When this block is fortuitously recorded in asymptomatic patients, pacemaker implantation is not indicated.